LayerLock: Layer-Wise Collision-Free Multi-Robot Additive Manufacturing Using Topologically Interlocked Space-Filling Shapes. (November 2022) - Krishnamurthy, Vinayak; Poudel, Laxmi; Ebert, Matthew; Weber, Daniel H.; Wu, Rencheng; Zhou, Wenchao; Akleman, Ergun; Sha, Zhenghui
Abstract: We present LayerLock, an approach for synchronous multi-robot additive manufacturing (cooperative 3D printing or C3DP). Our approach is based on Delaunay Lofts, a class of topologically interlocked shapes that are generated by stacking layers of Voronoi partitions of a set of moving Voronoi sites based on wallpaper symmetries. Our approach is based on two key insights. First, each layer of a Delaunay Loft is simply a tessellation of convex polygons allowing for easy division of cells for collision-free simultaneous material deposition. Second, the unique transition of Voronoi cells along the layers naturally leads to topological interlocking, thereby providing better energy absorption ability compensating for the loss of structural strength due to segmented printing. In this work, we constrain our current investigation to a two-robot system and develop the LayerLock algorithm consisting of three steps: (1) a distance-based division of the Voronoi cells at each layer of the Delaunay Loft, (2) a moving-front strategy for determining the sequence of cells for each robot, and (3) print path generation based on the cell sequence, which allows synchronous collaboration. We evaluate our algorithm for a range of geometric parameters such as part orientation and cell resolution. We also demonstrate it practically using a two-robot cooperative 3D printing platform. Highlights: An approach for synchronous multi-robot additive manufacturing. The approach uses layer-wise printing of polygonal cells that interlock topologically when stacked vertically. An algorithm is developed for volume-partitioning, cell sequencing, and path planning for a two-robot system. The algorithm is evaluated numerically for part orientation and cell resolution. The approach is demonstrated physically by printing interlocked structures using a two-robot system.